Evaluation of Polylactic Acid Polymer as a Substrate in Rectenna for Ambient Radiofrequency Energy Harvesting - Pangsui Usifu Linge; Tony Gerges; Pascal Bevilacqua; Jean-Marc Duchamp; Philippe Benech; Jacques Verdier; Philippe Lombard; Michel Cabrera; Pierre Tsafack; Fabien Mieyeville; Bruno Allard (Journal of Low Power Electronics and Applications, 2023)
This work details the design and experimental characterization of a 2D rectenna for scavenging radio frequency energy at 2.45 GHz (WiFi band), fabricated on polylactic acid polymer (PLA) using a plastronics approach. PLA is the RF substrate of both antenna and rectifier. The two transmission line (TTL) approach is used to characterize the substrate properties to be considered during design. A linearly polarized patch antenna with microstrip transmission feeding is connected to a single series diode rectifier through a T-matching network. The antenna has simulated and measured gain of 7.6 dB and 7.5 dB, respectively. The rectifier has a measured DC output power of 0.96 <semantics>μ</semantics>W at an optimal load of 2 k<semantics>Ω</semantics> under RF input power of −20 dBm at 2.45 GHz. The power conversion efficiency is 9.6% in the latter conditions for a 54 × 36 mm patch antenna of a 1.5 mm thick PLA substrate obtained from additive manufacturing. The power conversion efficiency reaches a value of 28.75% when the input power is −10 dBm at 2.45 GHz. This corresponds to a peak DC power of 28.75 <semantics>μ</semantics>W when the optimal load is 1.5 k<semantics>Ω</semantics>. The results compare significantly with the ones of a similar rectenna circuit manufactured on preferred RF substrate.